2017
DOI: 10.1093/ofid/ofx163.788
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Appointment Adherence of Outpatient Parenteral Antimicrobial Therapy (OPAT) Patients

Abstract: BackgroundOutpatient parenteral antibiotic therapy (OPAT) is a safe and effective care delivery system that allows patients to receive intravenous (IV) antibiotic therapy outside of the hospital. OPAT patients require frequent follow-up appointments for clinical and laboratory monitoring of common adverse outcomes of any IV antibiotic administration such as line infections, adverse drug events, and reinfection. Despite the known importance of clinical monitoring, patient factors that influence adherence to OPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Finally, the low rate of treatment completion, high rate of loss to follow-up, and ability to track patients only in settings linked to our EHR hinder our ability to confidently assess the clinical effectiveness of dalbavancin. Unfortunately, this low rate of engagement in care and follow-up is common among PWUD [7, 16] and highlights the challenges in caring for this population. Among 101 housed and homeless PWID receiving OPAT without dalbavancin from our institution, we note a similar rate of clinical cure (49%) and a high rate of unknown outcome (47%) due to loss to follow-up [17].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the low rate of treatment completion, high rate of loss to follow-up, and ability to track patients only in settings linked to our EHR hinder our ability to confidently assess the clinical effectiveness of dalbavancin. Unfortunately, this low rate of engagement in care and follow-up is common among PWUD [7, 16] and highlights the challenges in caring for this population. Among 101 housed and homeless PWID receiving OPAT without dalbavancin from our institution, we note a similar rate of clinical cure (49%) and a high rate of unknown outcome (47%) due to loss to follow-up [17].…”
Section: Discussionmentioning
confidence: 99%
“…24 Another study of 80 patients assessed OPAT appointment adherence and found that 84% of patients, who received at least one appointment reminder, came to follow-up appointments. 25 To our knowledge, no data have described adherence to self-administered IV antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to PO antibiotics when measured using the Medication Event Monitoring System (Aprex, Union City, CA, USA) was reported to be between 18% and 57% . In comparison, adherence to antibiotics for patients receiving outpatient parenteral antibiotic therapy (OPAT) is consistently at or above 80% .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations